Advances in Microfluidics and Nanofluids 2021
DOI: 10.5772/intechopen.96991
|View full text |Cite
|
Sign up to set email alerts
|

Solar Thermal Conversion of Plasmonic Nanofluids: Fundamentals and Applications

Abstract: Plasmonic nanofluids show great interests for light-matter applications due to the tunable optical properties. By tuning the nanoparticle (NP) parameters (material, shape, and size) or base fluid, plasmonic nanofluids can either absorb or transmit the specific solar spectrum and thus making nanofluids ideal candidates for various solar applications, such as: full spectrum absorption in direct solar absorption collectors, selective absorption or transmittance in solar photovoltaic/thermal (PV/T) systems, and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 116 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…m and C P are used to depict the mass flow rate in kg/s and specific heat capacity of the working fluid. The coefficient of collector efficiency is represented using F , which can be calculated using Equation (7) [42]…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…m and C P are used to depict the mass flow rate in kg/s and specific heat capacity of the working fluid. The coefficient of collector efficiency is represented using F , which can be calculated using Equation (7) [42]…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Their study concluded that the optical properties of the copper@carbon nanoparticle were significantly affected by their radius and shell thickness. The study by Chen et al [7] specifically experimented with plasmonic nanofluids and stated that by tuning their shape and size, they can absorb and transmit a specific spectrum.…”
Section: Introductionmentioning
confidence: 99%